IPTEK BAGI PRODUK EKSPOR UKM PENGRAJIN ROTAN “LEU BAGO AWE” - Ully Muzakir (Jurnal Visipena, 2017)
The objective of this program is to boost export growth of rattan handicraft products in Aceh Besar regency, namely UKM "Leu Bago Awe" through improved management and product quality. The program also aims to accelerate the transfer of technology and management from STKIP Bina Bangsa Getsempena Banda Aceh as the implementer of program to SMEs "Leu Bago Awe" as an industrial society as well as developing link & match between STKIP Bina Bangsa Getsempena Banda Aceh, SMEs, Aceh Besar District Government and wide community. The method of implementation of this program includes: training and mentoring with activities such as: product design training, tool production training, knitting training for standard size and shape, production management training, administration and finance training, equipment procurement, participation in exhibition, web creation, arrangement of raw material storage space, goods and show room, cooperate with DJPEN and IPR processing. The result of this program is the creation of products that have export quality standards and have a product marketing system online so that it can cover all countries. Abstrak Tujuan program ini adalah memacu pertumbuhan ekspor produk kerajinan rotan di Kabupaten Aceh Besar yaitu UKM “Leu Bago Awe” melalui peningkatan manajemen dan kualitas produk. Program ini juga bertujuan mempercepat alih teknologi dan manajemen dari STKIP Bina Bangsa Getsempena Banda Aceh sebagai pelaksana program kepada UKM “Leu Bago Awe” sebagai masyarakat industri disamping juga mengembangkan link & match antara STKIP Bina Bangsa Getsempena Banda Aceh, UKM, Pemerintah Kebupaten Aceh Besar dan masyarakat luas. Metode pelaksanaan program ini meliputi: pelatihan dan pendampingan dengan kegiatan antara lain: pelatihan mendesain produk, pelatihan penggunaan alat produksi, pelatihan perajutan untuk standar ukuran dan bentuk, pelatihan manajemen produksi, pelatihan administrasi dan keuangan, pengadaan peralatan, keikutsertaan dalam pameran, pembuatan web, penataan ruang penyimpanan bahan baku, barang dan show room, menjalin kerja sama dengan DJPEN serta pemrosesan HKI. Hasil dari program ini adalah terciptanya produk-produk yang memiliki standar mutu ekspor serta memiliki sistem pemasaran produk secara online sehingga dapat mencakup seluruh negara. Kata kunci: Kerajinan, Ekspor, Rotan